2019
DOI: 10.1002/ece3.5249
|View full text |Cite
|
Sign up to set email alerts
|

Immune and environment‐driven gene expression during invasion: An eco‐immunological application of RNA‐Seq

Abstract: Host–pathogen associations change rapidly during a biological invasion and are predicted to impose strong selection on immune function. It has been proposed that the invader may experience an abrupt reduction in pathogen‐mediated selection (“enemy release”), thereby favoring decreased investment into “costly” immune responses. Across plants and animals, there is mixed support for this prediction. Pathogens are not the only form of selection imposed on invaders; differences in abiotic environmental conditions b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
3
19
0
Order By: Relevance
“…While studies of cane toads have shown that traits may have curvilinear responses with distance along an invasion gradient [36][37][38], here, I provide a clear demonstration across two transects that the trait of dispersal capacity itself can have a nonlinear relationship with distance from the core and, thus, its characterization requires more than two observations (e.g. core versus frontline).…”
Section: Discussionmentioning
confidence: 68%
“…While studies of cane toads have shown that traits may have curvilinear responses with distance along an invasion gradient [36][37][38], here, I provide a clear demonstration across two transects that the trait of dispersal capacity itself can have a nonlinear relationship with distance from the core and, thus, its characterization requires more than two observations (e.g. core versus frontline).…”
Section: Discussionmentioning
confidence: 68%
“…Morphological and physiological traits underlie this accelerated expansion, yet it is also clear that behavioural traits have evolved across this invasion; western cane toads exhibit bolder behaviour than eastern toads (Gruber et al, ). Notably, these changes have occurred despite low genetic diversity in Australian toads (Lillie, Shine, & Belov, ; Selechnik, Richardson, Shine, Brown, & Rollins, ; Slade & Moritz, ). Environmental and intrinsic factors (e.g., genetic components) that may affect behavioural traits have been previously studied (Rollins, Richardson, & Shine, ; Selechnik, Richardson, Shine, DeVore, et al, ; Urban et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and physiological traits underlie this accelerated expansion, yet it is also clear that behavioural traits have evolved across this invasion; western cane toads exhibit bolder behaviour than eastern toads (Gruber et al, 2017). Notably, these changes have occurred despite low genetic diversity in Australian toads (Lillie, Shine, & Belov, 2014;Selechnik, Richardson, Shine, Brown, & Rollins, 2019;Slade & Moritz, 1998).…”
mentioning
confidence: 99%
“…Conversely, at the invasion‐front, where there is a strong evolutionary pressure for dispersal ability via both natural selection and spatial sorting (Brown et al, 2014; Phillips & Perkins, 2019), increased host resistance might be favoured if parasite infection reduces dispersal ability. Moreover, some sets of immune genes are upregulated at the invasion‐front (Selechnik et al, 2019a), suggesting that heightened, possibly non‐specific, immune responses arising from exposure to other pathogens or conditions at the invasion‐front may increase resistance of toads (Brown et al, 2018; Mayer et al, 2021). This hypothesis is supported by the reduced longevity of larvae when exposed to skin secretions of toads from the invasion‐front.…”
Section: Discussionmentioning
confidence: 99%